2012
DOI: 10.7324/japs.2012.2821
|View full text |Cite
|
Sign up to set email alerts
|

Tea and Mint Extracts Modulate the HSP70 Expression in Preeclamptic Placental Explant

Abstract: Heat shock protein 70 is a molecular chaperone which expressed during oxidative stress to protect the cell from damage. Preeclampsia is a hypertensive disorder with an oxidative stress imbalance. Antioxidant defenses appear to be depleted during preeclampsia resulting in increased oxidative stress. Various alternative medicines are employed to increase the endogenous antioxidant level during preeclampsia. The aim of the present study was to determine the modulatory effect of medicinal plants, Camellia sinensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Considering our results, piglets fed sunflower oil plus verbascoside diet presented a level of Hsp70 comparable to the control group, whereas piglets fed sunflower oil diet revealed a higher level of Hsp70 (+75 and +62% compared with control and sunflower oil plus verbascoside diets, respectively), therefore suggesting the protective role of verbascoside in hepatic cells. In fact, as previously observed, many oxidizing agents have been shown to result in Hsp induction, and treatment of cells with antioxidants attenuates the response (Gorman et al, 1999;Padmini et al, 2012). Verbascoside are able to scavenge free radicals and reactive oxygen molecules such as superoxide anion, nitric oxide, and hydroxyl radical (Zhao et al, 2009) but the mechanism through which verbascoside acts as a protective agent for hepatocytes, decreasing the level of Hsp70, remain to be investigated.…”
Section: Discussionmentioning
confidence: 92%
“…Considering our results, piglets fed sunflower oil plus verbascoside diet presented a level of Hsp70 comparable to the control group, whereas piglets fed sunflower oil diet revealed a higher level of Hsp70 (+75 and +62% compared with control and sunflower oil plus verbascoside diets, respectively), therefore suggesting the protective role of verbascoside in hepatic cells. In fact, as previously observed, many oxidizing agents have been shown to result in Hsp induction, and treatment of cells with antioxidants attenuates the response (Gorman et al, 1999;Padmini et al, 2012). Verbascoside are able to scavenge free radicals and reactive oxygen molecules such as superoxide anion, nitric oxide, and hydroxyl radical (Zhao et al, 2009) but the mechanism through which verbascoside acts as a protective agent for hepatocytes, decreasing the level of Hsp70, remain to be investigated.…”
Section: Discussionmentioning
confidence: 92%
“…It is well known that many oxidizing agents cause the induction of Hsp and that the treatment of cells with antioxidants attenuates the response to stress (Padmini et al, ). Our results are consistent with the observations described by Di Giancamillo et al (), that showed the levels of Hsp70 were decreased in pigs fed a diet supplemented with a natural verbascoside extract, compared with pig fed a high‐fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Green tea extract also showed some protective effects to testis based on rats' study with malathion-induced testicular oxidative [35]. The plant also affected germ cells in the placenta significantly, due to the recovery of cellular homeostasis, through effective antioxidant capacity and prevention of cell damage during stressful conditions [36]. Selenium-containing polysaccharides in tea (Se-GTPs) triggered apoptosis pathways of mitochondrial with increased Bax/Bcl-2 ratio, caspase-3, and caspase-9 in MCF-7 cells [37].…”
Section: Camellia Sinensismentioning
confidence: 99%